Traditional Chinese Medicine nursing of a patient with type 2 diabetes complicated with hypertension (1例2型糖尿病合并高血压患者的中医特色护理体会) - ZHANG Ji (张继); LIU Ai (刘爱); ZHANG Min (张敏); ZHAO Lina (赵丽娜); MING Yue (明月); ZUO Lin (左琳); FENG Ying (冯莹); ZHAO Zitong (赵紫彤) (中西医结合护理)
This article summarized the Traditional Chinese Medicine nursing practice of a case of type 2 diabetes with hypertension during hospitalization. On the basis of western medicine treatment, the intervention was carried out in combination with Traditional Chinese Medicine nursing techniques such as auricular acupoint pressing pills, acupoint application, and Traditional Chinese medicine cream and rubbing, which fully played the characteristics and advantages of Traditional Chinese Medicine technology, effectively controlled the patient's blood pressure and blood glucose, and improve the patient's quality of life. (本文总结1例2型糖尿病合并高血压患者的中医特色护理经验。基于护理评估和中医辨证, 在病情监测、饮食指导、药物管理等常规干预基础上, 配合耳穴压丸、穴位贴敷、中药膏摩等中医护理技术进行干预, 有效控制患者血压、血糖, 提高患者生活质量。)